AKSIOLOGI HAM TERHADAP PEMAHAMAN PESERTA DIDIK MENGENAI KEBEBASAN BERPENDAPAT PADA SISWA KELAS 10 di MADRASAH ALIYAH SWASTA AL-FALLAH - Yolanda Alfira Febriana; Della Gousmantari; Harni Hermayana; Hulfayatullayly; Aqilah Deani Alfarosa; Haerul Alfin; Edy Herianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the axiology of human rights (HAM) in improving students' understanding of freedom of speech. Freedom of speech is one of the fundamental rights that needs to be understood and applied responsibly by everyone. This study uses a qualitative descriptive approach, where data is obtained through observation, interviews, and text analysis. The research participants consisted of 26 students and 1 teacher. The results of the study showed that most students understood freedom of speech as a right that everyone has. In addition, it was found that there was a good relationship between the axiology of HAM and students' attitudes in expressing opinions during discussions in class.